Efektifitas Penggunaan Metode Guidance and Counselling Mereduksi Kecemasan Keluarga Menghadapi Pelaksanaan Imunisasi Ganda - hari, Munto (Medical : Jurnal Kesehatan dan Kedokteran, 2024)
The implementation of double immunization requires good communication and support from all parties, including the target families as the main subjects. However, many factors influence its success, such as mothers feeling afraid of side effects after immunization, which causes anxiety. Health workers have taken many approaches to reduce mothers' anxiety levels individually, including through guidance and counseling methods with a behavioral approach. This study aims to determine the effectiveness of the guidance and counseling method in reducing family anxiety regarding the implementation of double immunization in the working area of the Cijulang Health Center, Pangandaran District, West Java Province. The type of research used is an experiment involving an intervention to convey messages about double immunization through individual guidance and counseling methods to mothers of infants targeted for double immunization in two stages. The first stage involved measuring the level of family anxiety before the intervention with the guidance and counseling method, and the second stage involved remeasuring the level of family anxiety. The results were analyzed by comparing anxiety levels before and after the intervention. The study population consisted of 309 families. Using the Slovin calculation technique, a sample size of 76 families was determined, distributed proportionally across 7 villages. The results of the study indicate that the guidance and counseling method is effective in reducing family anxiety regarding the implementation of double immunization in the working area of the Cijulang Health Center, Pangandaran District, West Java Province, with a Z-value of 2850.00 and an Asymp.Sig (2-tailed) value of 0.00.